The Urhobo-Ndokwa Relations: Analysing the Core Delta Claims in an era of State Creation Agitation - Usman, Chukwudi; Opone, Paul O. (NIU Journal of Humanities; Vol 10 No 4 (2025): NIU Journal of Humanities, Vol. 10 No. 4, December 2025DO - 10.58709/niujhu.v10i4.2350, 2025)
The research examines the relationship between the Urhobo and Ndokwa ethnic nationalities in Delta State. Throughout history, the Urhobo have asserted that the Ndokwa ethnic minority is part of what they define as the core Delta. Consequently, they argue that Ndokwa should be incorporated into the authentic Delta State, thereby excluding the other Western Igbo groups (Enuani and Ika) known as Anioma, with whom they share socio-cultural connections. This study seeks to examine the origins of the Ndokwa and Urhobo peoples and their connections that may have led to such assertions. The research relies on a combination of primary and secondary sources to achieve its objectives. The approach utilises a descriptive historical reconstruction methodology for data analysis. The research posits that there is a lack of evidence indicating a connection between the Urhobo and Ndokwa; instead, the association leans towards the Western Igbo groups, all of whom trace their origins to the Igbo east of the Niger, primarily due to linguistic factors and other elements of cultural heritage. The research further reveals that the enduring relationship between the adjacent Urhobo and Ndokwa communities, alongside colonial influences, likely contributed to the emergence of such a claim. Of greater significance, the presence of crude oil deposits in Ndokwa land raises the possibility that, should the core Delta aspiration materialise, the Urhobo would seek to assert control over this wealth, particularly in light of the mono-cultural economic framework currently in operation in Nigeria. Keywords: Urhobo, Ndokwa, Origin, Core Delta, State Creation.